2016
DOI: 10.1785/0120150320
|View full text |Cite
|
Sign up to set email alerts
|

Source‐Scaling Relations of Interface Subduction Earthquakes for Strong Ground Motion and Tsunami Simulation

Abstract: The recording on high-resolution broadband seismic networks of several great interface subduction earthquakes during the last decade provide an excellent opportunity to extend source-scaling relations to very large magnitudes and to place constraints on the potential range of source parameters for these events. At present, there is a wide range of uncertainty in the median rupture areas predicted for any given seismic moment by current relationships between magnitude and rupture area for subduction interface e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
4
32
1
1
Order By: Relevance
“…Regardless of whether or not stress drop is scale-invariant, the A ∝ M 2=3 0 scaling has been observed to be consistent with empirical scaling relationships (Wells and Coppersmith, 1994;Somerville et al, 1999;Hanks and Bakun, 2002;Murotani et al, 2008;Leonard, 2010;Skarlatoudis et al, 2016). On the other hand, several studies reported that L grows faster with increasing magnitude (M w > 6) compared to the growth of W (e.g., Mai and Beroza, 2000;Henry and Das, 2001;Papazachos et al, 2004;Blaser et al, 2010;Leonard, 2010).…”
Section: Empirical Scaling Laws For Rupture Dimensionssupporting
confidence: 68%
See 2 more Smart Citations
“…Regardless of whether or not stress drop is scale-invariant, the A ∝ M 2=3 0 scaling has been observed to be consistent with empirical scaling relationships (Wells and Coppersmith, 1994;Somerville et al, 1999;Hanks and Bakun, 2002;Murotani et al, 2008;Leonard, 2010;Skarlatoudis et al, 2016). On the other hand, several studies reported that L grows faster with increasing magnitude (M w > 6) compared to the growth of W (e.g., Mai and Beroza, 2000;Henry and Das, 2001;Papazachos et al, 2004;Blaser et al, 2010;Leonard, 2010).…”
Section: Empirical Scaling Laws For Rupture Dimensionssupporting
confidence: 68%
“…Earthquake source-scaling relations provide empirical equations that link observable source parameters to each other. Such scaling relations not only provide insight into earthquake mechanics (e.g., Scholz, 1982;Romanowicz, 1992;Wells and Coppersmith, 1994;Mai and Beroza, 2000;Blaser et al, 2010;Skarlatoudis et al, 2016) but also constitute an essential ingredient in seismic-tsunami-hazard studies (e.g., Stafford, 2014;De Risi and Goda, 2016). However, available databases are limited, whereas uncertainties in the source parameters (primarily rupture length L, rupture width W, average displacement D, and seismic moment M 0 ) are hardly considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stresses were calculated in a 3‐D tensorial way for a half space model by using the formulations given by Okada []. The rupture area, for each analyzed earthquake of the series, is given by an empirical relation, where the aspect ratio explicitly depends on the moment magnitude [ Skarlatoudis et al , , Table 4]. Additionally, we performed the same analysis by using the scaling relations by Wells and Coppersmith [] for comparison.…”
Section: Methodsmentioning
confidence: 99%
“…There are several magnitude scaling relationships available in the literature that are derived from global observation of earthquakes on the plate interface of SZ (Papazachos et al, 2004;Strasser et al, 2010;Murotani et al, 2013;Goda et al, 2016;Skarlatoudis et al, 2016). Of these, Skarlatoudis et al (2016) compiled an updated database of interface earthquakes that occurred worldwide in last decade in the major SZs (e.g., 2004 M 9.1 Sumatra, 2010 M 8.8 Chile, 2011M 9.0 Japan earthquake) and proposed new and improved source scaling laws with reduced uncertainty compared to other currently available source scaling laws for subduction earthquakes. Once the appropriate source magnitude and scaling laws are identified, the final step is to perform the earthquake and tsunami simulations for a multiple logic-tree branch.…”
Section: Multi-hazard Logic-tree Modelmentioning
confidence: 99%